Tangled Lands: Burma and India's Unfinished Separation, 1937–1948 - Guyot-Réchard, Bérénice (The Journal of Asian studies, 2021)
In 1937, Burma formally separated from India. The separation might seem self-evident, given India and Burma's framing as distinct, bounded spaces. Yet, in the Patkai mountains straddling them, separation was a complex process with only a murky sense of finality, more problematic and contested than generally acknowledged. The border ran through similar groups and complex networks, which posed recurring problems for local inhabitants and frontier officials. As independence neared, colonial officials unsuccessfully tried to reshape the Patkai's territorialization. Viewed from the Patkai, the narrative of an amiable divorce between two ill-suited partners crumbles. The separation was one of several partitions that created bounded spaces across South Asia during the twentieth century. Seeing Burma and India as distinct others privileges spatio-cultural hierarchies rooted in colonial frameworks, assimilated by postcolonial political arrangements and nation-state-centric scholarship. This article foregrounds the need to explore how India and Burma were made against one another and recover alternative spatialities.